Antibacterial Effect Of Kaempferia Galanga L Extract On Lactobacillus Acidophilus –In Vitro - Josi Saraswati; Annisa Septalita; Arini Bovita. N (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2013)
Introduction: Lactobacillus acidophilus is one of the bacteria causes dental caries. The previous study has shown that Kaempferia galanga extract has a potential to inhibit the growth of Lactobacillus acidophilus.Objective: To determine the antibacterial effect of Kaempferia galanga extract to Lactobacillus acidophilus.Methods:Kaempferia galanga is extracted in 3 different solvents:dichlormethane, ethanol, and aquades. For each solvent, 0.2 μl Kaempferia galanga extractdroped into 6 mm steril paper dics. 0.1 ml Lactobacillus acidophilus inoculated on MRS agar. Each disc contains extract were impragnated into the agar media, then incubated at 370C for 24 hours, and inhibition zone measured.Results: Mean scores of Kaempferia galanga extract in 3 different solvents are: Kaempferia galanga (dichlormethane) is 1.6400; Kaempferia galanga (ethanol) is 1.7440; Kaempferia galanga extract is 1.6600; boiled Kaempferia galanga is 1.7000. Using Mann-Whitney Test, the results are: negative controls have no inhibition effect on Lactobacillus acidophilus compaired to Kaempferia galanga extract, comparation of those 4 Kaempferia galangal treatments shows no significant difference, those 4 Kaempferia galanga treatments compaired to erythromycin antibacterial effect shows significant difference, otherwise 4 Kaempferia galanga treatments compaired to penicillin shows no significant difference except Kaempferia galanga (ethanol).Conclusions: Kaempferia galanga extract can kill Lactobacillus acidophilus. Inhibition effect of Kaempferia galanga extract has no significant difference to penicillin but lower inhibition effect than erythromycin. The Kaempferia galanga extracts showed better antibacterial activity than penicillin.